Environmentalism unbound : exploring new pathways for change - Gottlieb, Robert, 1944- (Urban and industrial environments., 2001)
"In Environmentalism Unbound, Robert Gottlieb proposes a new strategy for social and environmental change that involves reframing and linking the movements for environmental justice and pollution prevention. According to Gottlieb, the environmental movement's narrow conception of environment has isolated it from vital issues of everyday life, such as workplace safety, healthy communities, and food security, that are often viewed separately as industrial, community, or agricultural concerns. This fragmented approach prevents an awareness of how these issues are also environmental issues."--Jacket